Recursos Didácticos Comunicativos Y Audiovisuales Para La Enseñanza-Aprendizaje Del Idioma Inglés A Través De Aulas Virtuales - Rolando, Armas Pesantez Paul; Geovanny, Armas Pesantez Washington; Hernán, Salazar Calderón Edison; Oswaldo, Guadalupe Bravo Luis; Isaac, Orozco Yánez Gabriel (European Scientific Journal, ESJ, 2017)
The purpose of the current research was the implementation of didactic audiovisual and communicative resources through a virtual classroom for the teaching-learning of English language, aimed to the first level students Languages School at Universidad Nacional de Chimborazo due to the lack of didactic material helping in the development of activities and tasks into the classroom. This fact impedes teachers and students reaching a higher level in the English Language teaching-learning process, this situation made necessary the implementation of resources adaptive to the pedagogical context and planned through a content manager or virtual classroom. The current research is quasi experimental, bibliographic, documental and descriptive which was applied to a sample where it was necessary to consider an initial knowledge diagnose before applying the communicative and audiovisual resources, then it was necessary to carry out an evaluation at the end of it. It was also necessary to use a set of activities based on communicative and audiovisual resources framed within the micro curriculum guidelines with schedules and contents that were evaluated through questionnaires and a checklist. The instruments for collecting information allowed obtaining data in both pre-test and post-test. These qualifications were compared through a statistical test that allowed concluding that the use of the mentioned resources improved the English language teaching, at the same time it was possible to recommend its use within the curriculum for the First Level of the Languages Major.